Association of Pre-Operative Vitamin D Levels and Severity of Fracture among Orthopedic Trauma Patients in A Single, Tertiary-Level Hospital - Christian Julius P. Mendoza MD, DPBO (SAGE Publishing, 2021)
Background/Purpose The high prevalence of hypovitaminosis D among trauma patients have been related to risk of fractures, falls, non-union and poor operative outcomes. There is limited evidence that ties up Vitamin D levels with fracture severity. The objective of this study is to determine the association of pre-operative Vitamin D levels and fracture severity. Methods This was a retrospective, cross-sectional study of patients with extremity fractures classified according to the AO Trauma classification system with baseline pre-operative vitamin D levels. The association between vitamin D levels and fracture severity of surgically treated trauma patients were analyzed. Sub-group analysis was performed on patients without osteoporosis and those patients who suffered from low-energy trauma. Results Ninety-six (96) patients were included. Those with severe fractures (AO -C fractures, 31B1.3/B2.3 and 31A3) were associated with lower Vitamin D levels (µ  =  17.87 µg/mL) (p < 0.001). There was a strong, positive significant correlation ( r s (4)  =  .426, p   =  < 0.001) between hypovitaminosis D and increasing fracture severity. This significant association of hypovitaminosis D with worse fracture patterns remains in the patient sub-group without osteoporosis ( p   =  0.030), and in those who sustained low-mechanism injuries ( p < 0.001). Conclusion We present initial evidence that low pre-operative Vitamin D level is associated with increasing fracture severity at the time of injury. Early detection, surveillance and management of low vitamin D levels can lead to drastic changes in the holistic approach to fracture prevention and treatment.